Implementasi Kebijakan Penanganan Stunting di Desa Tamansari Kecamatan Jatinegara Kabupaten Tegal - Nugroho, Hari (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2023)
Handling stunting is part of the human resource development strategy to produce a superior generation. These efforts include specific nutrition interventions and sensitive nutrition, which in their implementation require support from all parties, including the village government. Handling stunting in this village is inseparable from how the policy is implemented. The purpose of this study is to analyze the implementation of stunting management policies in Tamansari Village, Kecamatan Jatinegara, Kabupaten Tegal and determine the supporting and inhibiting factors. The results of the study shows that the stunting management policy in Tamansari Village is still in progress. This means that problems related to coordination, funding and participation from village government officials and other relevant stakeholders are still the main problems. The Desa Tamansari Government has only accommodated the policy for handling stunting toddler in the APBDes after the issuance of the Decree of the Tamansari Village Head Number 5 of 2022 concerning the Establishment of the Tamansari Village stunting acceleration team (TPPS). Specific nutrition interventions for health programs for the target group of pregnant women, breastfeeding mothers, newborns, and infants under the age of two have basically been implemented for a long time through posyandu activities coordinated by village midwives, posyandu cadres, and family planning extension cadres. However, these activities are not in the context of handling stunting toddlers, but regular health service activities with the Health Office as the leading sector. In sensitive nutrition interventions, there is no intensive coordination between the village government and the social environment. Supporting factors for the handling of stunting in Tamansari Village include the support of the village government, the economic level of the target group not including poor families, so that the nutritional intake needs of children and mothers can actually be fulfilled independently and good social environmental conditions strengthen community participation in sensitive nutrition interventions and nutrition interventions. specifically in the management of stunting. The main inhibiting factor lies in the lack of communication and knowledge from the village government and residents regarding stunting and the impact of stunting, followed by inadequate budget support for handling stunting toddlers. Keywords: Implementation, Stunting